Elements of financial risk management - Christoffersen, Peter F. (Amsterdam ; Boston : Academic Press, 2003)
This book pinpoints key features of risk asset returns and captures them in tractable statistical models.
Accompanying CD-ROM contains Excel files with answers to chapter exercises, as well as Excel spreadsheets with data underlying the exercises.
Includes bibliographical references and index.
osa 05/06/14
Loans
Keywords: Financial risk management; Risk management; Modeling -correlation, volatility, option risk; Financial returns